2023
DOI: 10.3389/fpubh.2022.1086849
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating co-circulation of seasonal influenza and COVID-19 pandemic in the presence of vaccination: A mathematical modeling approach

Abstract: The co-circulation of two respiratory infections with similar symptoms in a population can significantly overburden a healthcare system by slowing the testing and treatment. The persistent emergence of contagious variants of SARS-CoV-2, along with imperfect vaccines and their waning protections, have increased the likelihood of new COVID-19 outbreaks taking place during a typical flu season. Here, we developed a mathematical model for the co-circulation dynamics of COVID-19 and influenza, under different scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Such availability caused those who were hesitant to manifest their opinion with greater intensity. Despite the existence of COVID-19 variants circulating in Brazil, we did not encounter any manifestation of VH related to this issue (48).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Such availability caused those who were hesitant to manifest their opinion with greater intensity. Despite the existence of COVID-19 variants circulating in Brazil, we did not encounter any manifestation of VH related to this issue (48).…”
Section: Discussionmentioning
confidence: 51%
“…These initial manifestations express concerns with the source of the vaccine, i.e., with which laboratory is developing it, highlighting the need for the government to establish partnerships with research and production laboratories to provide as much information as possible. Subsequent evidence showed that some vaccines were imperfect or even had a declining protection index, thus favoring new COVID-19 outbreaks (48). In Brazil some politicians assured that the vaccine made contamination impossible, which increased VH when the first cases of contamination by COVID-19 of vaccinated people surfaced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, they have helped in the elimination of polio and the eradication of smallpox [ 26 ]. They hold the potential to protect humanity against morbidity and mortality from current and future epidemics [ 27 ]. Nonetheless, the distribution and allocation of vaccines to where they are needed the most in the world is a challenge.…”
Section: Problem Statementmentioning
confidence: 99%
“…The literature on epidemic models is extensive, with structure variables and vaccination elements. In our References, we have listed many of such works [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 …”
Section: Introductionmentioning
confidence: 99%